'Always momentary, fluid and flexible' : towards a reflexive excavation methodology - Hodder, Ian
ÇatalhÖyük, on the Konya Plain in south central Anatolia, in the 1960s became the most celebrated Neolithic site of western Asia: huge (21 hectares), with early dates, tightpacked rooms with roof access, exuberant mural paintings, cattle heads fixed to walls, dead buried beneath floors in collective graves.\\This site, as difficult to excavcate as it is strange, is the object of a pioneering application of the 'post-processual' approach, hitherto largely a matter of re-working and criticism outside the trench. The ÇatalhÖyük project director explains his approach, in which the conclusions as well as the work in early progress will be 'always momentary, fluid and flexible'.